DYSTOCIA IN CAPTIVE BONNET MONKEY A CASE REPORT - BIRADE, H S; YADAV, G B; BADGUJAR, C L; GAIKWAD, R V; KOLI, S S; DAGALI, N R; PALAMPALLE, H Y; GAIKWAD, S V (The Indian Journal of Animal Reproduction, 2023)
The present communication records the occurrence of dystocia in a Bonnet Monkey due to incomplete dilatation of cervix which was managed by caesarean section. ·